World Heritage: an approach to vernacular and earthen architecture - Bermudez, Teresa (2019)
World Heritage is an international concept established by the World Heritage Convention. However, what it means, how is evaluated, and conserved is still unclear even for heritage professionals and conservation experts. This article aims to clarify what does Outstanding Universal Value means and how its foundation stands to establish three key-pillars: criteria, integrity and authenticity, protection and management. Their compliance justifies why a nominated site becomes a World Heritage property. These three key-pillars are also analysed in the case of vernacular and earthen architecture World Heritage properties. The paper introduces the fact that vernacular architecture is underrepresented in the World Heritage list. As a result, a research was addressed regarding the analysis of different types of vernacular categories. This paper introduces the different paramaters that were identified considering the thematic approach introduced by the vernacular and earthen architecture framework: the landscape setting; the urban layout; the architecture features; and the building culture. A deeper comparative analysis regarding the diversity existing in vernacular and earthen architecture is being undertaken to contribute for the rising of nominations in this thematic area, therefore contributing for a more balanced, representative and credible World Heritage List.